The role of foresight in public policy: lessons from deliberative democracy and perspectival realism - Brian Galvin (European Journal of Futures Research)
Abstract Foresight plays an important role in public policy development. The foresight learning process brings together various actors in the policy community and incentivizes them to think about the future.  It encourages new ways of thinking and approaches to strategy and is a practical approach to using the future to inform decisions and actions in the present.  Foresight faces challenges in becoming embedded in the policy process.  One of these challenges is in establishing its epistemic authority when compared to natural science and social science disciplines.  This paper argues foresight can benefit from developments in political theory and philosophy of science.  Democratic deliberation is an approach to public discourse which emphasizes pluralism in debate and provides a detailed account of how reason-giving can add epistemic depth to foresight’s contribution to policy.  Perspectival realism is a theory in philosophy of science which identifies the interplay between separate epistemic communities as the key mechanism in scientific development.  The modal models that these epistemic communities create present a new way of understanding foresight’s study of the future and its part in the weave of scientific evidence, opinion and analysis that constitute policy development in a democratic society.